Validación del diseño de componentes de QuAM : un modelo de calidad para procesos ágiles - Pinto, Noelia (2016)
Work in software processes improvement is a step that companies in the Software Industry must take in order to increase the quality and capability of their processes and consequently, the quality of their products and services. This process improvement involves the adoption of both a quality model suitable to the characteristics of the company, and a methodology to guide the software development cycle. In this article, results of the validation process of QuAM (Quality Agile Model) are presented, an approach to the design of an integrated and flexible model in order to evaluate the quality development cycles based on the principles and practices of the agile approach